Efektivitas Kompres Daun Kubis (Brasscis Oleracia Var Capitata) dan Breastcare Terhadap Pengurangan Pembengkakan Payudara Ibu Nifas di Bpm Ade Kismi Bania - Pititika Sarpari; Lili Farlikhatun (Universitas Malahayati Lampung, 2024)
ABSTRACT Breast milk dams are a problem that often occurs at the beginning of the postpartum period, which can cause discomfort so that it becomes one of the obstacles in exclusive breastfeeding. Therefore, an effective method is needed to overcome this problem. Based on the results of a preliminary survey at BPM Ade Kismi Bania, out of 24 postpartum mothers, 17 postpartum mothers experienced breast swelling and 7 postpartum mothers did not experience breast swelling. Based on the above, the researcher is interested in conducting research entitled